Tire o racismo do seu Vocabulário - WELTER , CAROLINA; EDUARDA GUTH , MAÍSA; ZAIONCZ ROLOFF , MONIQUE; DA SILVA SANTOS , ROSITA (Salão do Conhecimento, 2021)
Carolina Welter2 , Maisa Guth3 , Monique Roloff4 , Rosita da Silva Santos5